Human Rights Archives and Research on Historical Memory: Argentina, Chile, and Uruguay - Bickford, Louis (Latin American Research Review, 2000)
[This research note discusses an emerging subfield of inquiry in the study of democratization in Latin America: a focus on the relationships between past human rights abuses and democratization processes. It outlines four sets of questions emerging around the themes of "historical memory" and "legacies of authoritarian rule." The study then examines documentary collections of major human rights nongovernmental organizations (HRNGOs) in Argentina, Chile, and Uruguay. The purpose of this endeavor is to provide researchers interested in studying the four issues with specific information on documents produced and currently held by the HRNGOs in the Southern Cone. The essay examines seven HRNGOs in Chile, ten in Argentina, and four in Uruguay, and ends with practical hints for researchers who wish to use these resources.]
Other Publications

The Nanjing Massacre in History and Historiography - Maier, Charles S. (University of California Press, 2000)
The Rape of Nanjing was one of the worst atrocities committed during World War II. On December 13, 1937, the Japanese army captured the city of Nanjing, then the capital of wartime China. According to the International Military Tribunal, during the ensuing massacre 20,000 Chinese men of military age were killed and approximately 20,000 cases of rape occurred; in all, the total number of people killed in and around the city of Nanjing was about 200,000. This carefully researched, intelligent collection of original essays considers the post-World War II treatment in China of the Nanjing Massacre and Japan. The book examines how the issue has developed as a political and diplomatic controversy in the five decades since World War II.In his introduction, Joshua A. Fogel raises the significant moral and historiographical issues that frame the other essays. Mark Eykholt then provides an account of postwar Chinese responses to the massacre. Takashi Yoshida assesses the attempts to downplay the incident and its effects, providing a revealing analysis of Japanese debates over Japan's role in the world and the continuing ambivalence of many Japanese toward their defeat in World War II. In the concluding essay, Daqing Yang widens the scope of the discussion by comparing the Nanjing historiographic debates to similar debates in Germany over the nature of the Holocaust.
Keywords: References - Boel et al. (2021); Archives and Human Rights

ISAD(G): General international standard archival description; adopted by the Committee on Descriptive Standards, Stockholm, Sweden, 19-22 Sept. 1999 - International Council of Archives (International Council on Archives, 2000)
Keywords: References - Boel et al. (2021); Archives and Human Rights

Arresting Nazi spies in Vichy France (1940–42) - Kitson, Simon (Intelligence and National Security, 2000)
Keywords: References - Boel et al. (2021); Archives and Human Rights

The right to restitution, compensation and rehabilitation for victims of gross violations of human rights and fundamental freedoms : - Bassiouni, M. Cherif (UN, 2000)
Keywords: References - Boel et al. (2021); Archives and Human Rights

Establishment of a Permanent Forum on Indigenous Issues - Economic and Social Council Resolution 2000/22 - Office of the High Commissioner for Human Rights (United Nations, 2000)
Keywords: References - Comma (2020 1-2); Archives and Human Rights

The Challenge of Human Rights – CHARLES MALIK and the Universal Declaration - Malik, Habib C. (The Centre for Lebanese Studies and I B Tauris & Co Ltd, 2000)
Charles Malik of Lebanon was a key player at the UN in this historical drama that extracted a set of universal human rights out of the chaos of antagonistic ideologies and clashing world-views. This book contains a distillation of his writings, interventions and reflections on the making of the Universal Declaration, the contentious issues grappled with along the way, some of the personalities involved in the process, and the laborious stages of the process itself.
Keywords: References - Comma (2020 1-2); Archives and Human Rights